Comparison of dynamic plantar support after a triple jump competition - Samper, J. M.; Bertucci, W. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Triple jump is an athletic event that requests specifically a balanced foot support in order to optimize the performance. The first ray of the foot (hallux and first metatarsal head) has an important function to propel the body during take off for the hop and the step. Dynamic foot pressure is a good indicator and it has been used in various studies to detect foot pathologies (Putti et al. 2010). A large consensus displays that normal feet have the greatest pressure located on the second and third metatarsal heads. Sanchez-Rodriguez et al. (2012) measured plantar pressures on 400 participants according to the type of foot with the FootScan platform (4096 sensors) operating at 150 Hz.